The productivity and economic value of sweet potato (Ipomea batatas) planted intercropped with satoimo taro (Colocasia esculenta (L.) Schott var. Antiquorum) with various levels of compost. Issue 1 (November 2021) - Syafiuddin, M; Jayadi, M; Rasyid, B; Busthanul, N
Abstract: Sweetpotato ( Ipomea batatas ), as a well-known plant and widely cultivated by farmers in South Sulawesi, if it is intercropped with satoimo taro ( Colocasia esculenta (L.) Schott var. Antiquorum) as a staple crop should be suspected of being able to be a 'safety' crop when there is a failure in taro plant—due to the relatively new and un-well-known plant. The study was aimed to know the productivity and economic value of sweet potato planted as an intercropped on the staple crop satoimo taro plantation with several levels of compost. The study used a randomized complete block design with four levels of manure compost, namely 400 grams, 800 grams, and 1200 grams per staple plant, which put into and mixed evenly in the plant hole, and 1200 grams per staple plant which mixed evenly in the beds, and three blocks. Sweet potatoes were planted between staple plants satoimo that arranged 20 plants in a bed of 500 cm x 110 cm in two rows. The parameters observed were yields of tuber per plant, size of tuber, number of tubers, and dry weight of tops. The results showed that there is no level of compost affected significantly. However, both of the levels of 1200 grams of compost which is filled into the plant hole, and 1200 grams of compost mixed in the beds tended to be higher than the others in tuber productivity. By economic valuations, the RC-ratio and RC-ratio indicated that planting intercropped sweet potato are beneficially in all levels and increased after the levels of compost. Cultivating sweet potato intercropped in the two kinds application of 1200 grams levels in the taro plantation is more recommended.